Expanding the clinical and immunological phenotypes and natural history of MALT1 deficiency - KOLUKISA, BURCU; ÖZEN, AHMET OĞUZHAN; BARIŞ, SAFA (My University, 2022)
Purpose MALT1 defciency is a combined immune defciency characterized by recurrent infections, eczema, chronic diarrhea, and failure to thrive. Clinical and immunological characterizations of the disease have not been previously reported in large cohorts. We sought to determine the clinical, immunological, genetic features, and the natural history of MALT-1 defciency. Methods The clinical fndings and treatment outcomes were evaluated in nine new MALT1-defcient patients. Peripheral lymphocyte subset analyses, cytokine secretion, and proliferation assays were performed. We also analyzed ten previously reported patients to comprehensively evaluate genotype/phenotype correlation. Results The mean age of patients and disease onset were 33±17 and 1.6±0.7 months, respectively. The main clinical fndings of the disease were recurrent infections (100%), skin involvement (100%), failure to thrive (100%), oral lesions (67%), chronic diarrhea (56%), and autoimmunity (44%). Eosinophilia and high IgE were observed in six (67%) and two (22%) patients, respectively. The majority of patients had normal T and NK cells, while eight (89%) exhibited reduced B cells. Immunoglobulin replacement and antibiotics prophylaxis were mostly inefective in reducing the frequency of infections and other complications. One patient received hematopoietic stem cell transplantation (HSCT) and fve patients died as a complication of life-threatening infections. Analyzing this cohort with reported patients revealed overall survival in 58% (11/19), which was higher in patients who underwent HSCT (P=0.03). Conclusion This cohort provides the largest analysis for clinical and immunological features of MALT1 defciency. HSCT should be ofered as a curative therapeutic option for all patients at the early stage of life. Keywords Inborn errors of immunity · primary immunodefciency · MALT1 · combined immune defciency · immune dysregulation · recurrent infections · skin involvement · failure to thrive · hematopoietic stem cell transplantation
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; İmmünoloji; Yaşam Bilimleri (LIFE); IMMUNOLOGY; Life Sciences (LIFE); Genel İmmünoloji ve Mikrobiyoloji; General Immunology and Microbiology; Immunology; Inborn errors of immunity; primary immunodeficiency; MALT1; combined immune deficiency; immune dysregulation; recurrent infections; skin involvement; failure to thrive; hematopoietic stem cell transplantation